Scoping review of interventions to increase VIA test uptake in Indonesia - Ramania, Ardhina; Pramudita, Bianda Dwida (Universitas Gadjah Mada, 2025)
Purpose: Cervical cancer remains a major public health concern in Indonesia. Although the VIA (Visual Inspection with Acetic Acid) screening program has been introduced, the national target of 75% coverage has not yet been achieved. Enhancing public participation requires more effective health promotion strategies. This study reviews public health intervention studies conducted in Indonesia aimed at increasing VIA screening uptake. Methods: Literature published between 2015 and 2025 in English and Indonesian was searched using PubMed and Google Scholar. Inclusion criteria focused on peer-reviewed intervention studies with transparent methodologies and outcome assessments related to VIA uptake. Qualitative studies and other types of studies not published in peer-reviewed journals were excluded from the analysis. Data were extracted and synthesized narratively based on the target intervention and outcomes. Results: From the 114 retrieved articles, 22 studies met the inclusion criteria. All were cross-sectional studies conducted across 12 Indonesian provinces, primarily in Java and Sumatra. Sample sizes ranged from 12 to 121 participants, totaling 1,278 individuals. Most studies targeted women (n = 19), while a few involved local women cadres (n = 2) or both (n = 1). Knowledge (n = 14) and attitude (n = 11) were the most frequently measured outcomes. All interventions (n = 22) reported positive results. Conclusion: These findings highlight a critical gap in health intervention strategies targeting women’s social support, especially husbands. Further research should design intervention research focusing on male partners and employ longitudinal designs to assess the long-term impact of these strategies on VIA test uptake.